Water relations of cassava cultivated under water-deficit levels - Pereira, Laís Fernanda Melo [UNESP]; Zanetti, Samara [UNESP]; Silva, Marcelo de Almeida [UNESP] (Springer Nature, 2018)
The tolerance of plants to water deficit involves a series of adaptive mechanisms; however, little is known about the physiological characteristics of cassava (Manihot esculenta Crantz), which is one of the most tolerant crops to adverse environmental conditions. The objective of this work was to evaluate the water relations in cassava plants subjected to different levels of water deficit. The treatments were conducted in three evaluation periods (0, 45 and 90 days after water deficit) and at three soil water tensions (− 10, − 40 and − 70 kPa), with five replicates. The plants were mainly affected at 45 days after the water deficit, with an increase of 42.9% in total chlorophyll content and 35.3% in carotenoid content in plants under a tension of − 70 kPa; however, these plants reduced by 30.8% chlorophyll a content at 90 days of the treatments. The water potential, relative water content and electrolyte leakage in the leaf were not altered by the soil water tension. There was an increase of 35.4% in stomatal density independent of soil water status at 90 days and of 16.0% under tensions of − 40 and − 70 kPa; however, the effective quantum efficiency of photosystem II and rate of electron transport were reduced. Cassava can maintain a leaf water potential close to − 0.3 MPa in the predawn and the integrity of the cell membranes in leaves under a soil water tension of up to − 70 kPa.
Keywords: Chlorophyll; Drought; Fluorescence; Manihot esculenta; Stomatal density; Water potential